Development of Cadastral Control Information System (CCIS) online - Omar, Abdullah Hisam; A. K., Abd. Majid; Keling, Noraidah (2005)
The cadastral reform is inevitable in this new millennium to handle and manage the constant proliferation to technological enhancement in computerization, information acquisition and communication. These will lead to the concept and realization of the Coordinated Cadastral System (CCS) for Malaysia. The most significant change that IT has brought about is the shift from conventional analogue data to digital data and consequently the introduction of the concept of online digital database. The usage of cadastral data control in CCS implementation is very important because all the measurement and cadastral control will be established according to cadastral control. The objectives of the study are to develop online-based cadastral control information system (CCIS) and to analyze the effectiveness of the system. The dataset include GPS station information, topography map, and digital cadastral database. The development of CCIS involves several phases such as data gathering, system design, interface development and physical development. ArcIMS was used in the CCIS development. The Development of CCIS Online is one of the initiatives to shift to E -Government. This is viewed as a long-term effort that will continue to evolve and improve. CCIS has been developed. A series of analysis indicates that CCIS was operating effectively